Complications of Colostomy Reversal in Patients with Imperforate ANUS - Amnah Azim, Nida Saeed, Nitu Kumara, Amema Hassan, Noorulain Chishti, Sadaf Chishti, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Colostomy reversal after definitive procedure in patients of Imperforate Anus (for example; PSARP) can be difficult and challenging for surgeon due to proximal and distal gut lumen discrepancy, short length of distal loop, difficult mobilization of stoma. These factors affect the anastomosis and anastomosis is done under tension due to these factors. Colostomies which are reversed under tension mostly results in anastomosis leakage and increases the morbidity and mortality rate. The objective of this study to assess postoperative outcome in terms of complications following colostomy closure in patients with imperforate anus. Material and Methods: This is a prospective study done at the Department of Pediatric Surgery, National Institute of Child Health Karachi during the period of 6months from December 2016 to June 2017. A Self- structured performa was used to collect the data of total 84 Patients who Underwent Colostomy Reversal after definitive procedure for imperforate anus . Data analyzed through SPSS version 20. A descriptive statistical analysis of continous and categorical variables were performed. Continuous data (like age) expressed as mean SD. The categorical data like gender, wound infections , anastomosis leakage expressed in frequency and percentages. Results: Out of total 84 children, majority 51 (60.7%) children were presented with ≤4 years of age (Mean age 4.15±3.12 years). Majority 55 (65.5%) children were presented with >8 kg of weight (Mean weight 13.31±6.00 kg). There were 41 (48.8%) males and 43 (51.2%) females. Intra-operative difficulty was found in 55 (65.5%) children. Postoperative complication showed that wound infections were observed in 10 (11.9%) children while frequency of anastomotic leakage was found in 12 (14.3%) children. Conclusion: Anastomotic leakage was found to be higher following colostomy closure in children with intra-operative difficulty due to proximal and distal gut lumen discrepancy, short length of distal loop and dense adhesions making difficult the mobilization of stoma.